Dynamics of the preterm gut microbiome in health and disease - Cuna, Alain; Morowitz, Michael J.; Ahmed, Ishfaq; Umar, Shahid; Sampath, Venkatesh (American journal of physiology: Gastrointestinal and liver physiology, 2021)
Advances in metagenomics have allowed a detailed study of the gut microbiome, and its role in human health and disease. Infants born prematurely possess a fragile gut microbial ecosystem that is vulnerable to perturbation. Alterations in the developing gut microbiome in preterm infants are linked to life-threatening diseases such as necrotizing enterocolitis (NEC) and late-onset sepsis; and may impact future risk of asthma, atopy, obesity, and psychosocial disease. In this mini-review, we summarize recent literature on the origins and patterns of development of the preterm gut microbiome in the perinatal period. The host-microbiome-environmental factors that portend development of dysbiotic intestinal microbial patterns associated with NEC and sepsis are reviewed. Strategies to manipulate the microbiome and mitigate dysbiosis, including the use of probiotics and prebiotics will also be discussed. Finally, we explore the challenges and future directions of gut microbiome research in preterm infants.